Rice Production, Policies, and Their Implications on Food Security Indonesia - Thailand Perspective - Yusuf, M.Asa`ari; Sundari, Sri; Purwanto, Ignatius Djoko; Kurnia, Ratih Rachma (PT FORMOSA CENDEKIA GLOBAL, 2024)
Rice serves as the primary commodity in the staple food supply in Asia, with Indonesia being the number one consumer of rice in Southeast Asia. Despite having the largest land area in Southeast Asia and being located on the equator, which provides favorable conditions for agriculture, Indonesia, particularly, imports rice from Thailand. The national agricultural sector in Indonesia has proven to be significant, but the country is considered lagging behind Thailand in terms of rice commodities. From an economic perspective, rice remains a strategic commodity, both for food security and the agricultural sector, especially for farmers. This article employs a qualitative descriptive method, focusing on the land area, the existence of agricultural banks, fair pricing, farming orientation, modernization of agricultural tools, and government policies. The research findings emphasize the need for the development of new rice varieties to address climate change and increase resistance to pests. It also stresses the importance of accurate fertilizer subsidies, vigilance regarding global food crises due to conflicts in Russia-Ukraine and the Middle East, and anticipated climate change impacts. Indonesia must play a role in future rice exports, considering the high agricultural potential in the country